2023
DOI: 10.3390/su151511694
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Student and Teacher Challenges in Smart Synchronous Hybrid Learning Environments

Adrián Carruana Martín,
Carlos Alario-Hoyos,
Carlos Delgado Kloos

Abstract: The COVID-19 pandemic has led to the growth of hybrid and online learning environments and the trend of introducing more technology into the classroom. One such change could be the use of smart synchronous hybrid learning environments (SSHLEs), which are settings with both onsite and online students concurrently, where technology plays a key role in sensing, analyzing, and reacting throughout the teaching and learning process. These changing environments and the incorporation of new technologies can place a gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…These suggestions are closely tied to the essence of AL. However, previous studies have simply suggested novel blended synchronous learning environments without considering AL [5,14]. Our study, in contrast, focused on AL, emphasizing the facilitation of interactions between learners by promoting facing behaviors.…”
Section: Introductionmentioning
confidence: 92%
“…These suggestions are closely tied to the essence of AL. However, previous studies have simply suggested novel blended synchronous learning environments without considering AL [5,14]. Our study, in contrast, focused on AL, emphasizing the facilitation of interactions between learners by promoting facing behaviors.…”
Section: Introductionmentioning
confidence: 92%